Pendekatan Sejarah Dalam Penelitian Hadits - Yudi Imana; Tajul Arifin (Yayasan Cendekia Gagayunan Indonesia, 2024)
This research is motivated by the importance of the historical approach in hadis studies to understand the context, background, and development of hadis transmission over time. This study aims to analyze the role of the historical approach in exploring the origins, authenticity, and validity of hadis through a chronological study. The research applies a historical approach, using literature review techniques and analysis of relevant hadis sources. Data is collected through the study of both classical and modern texts that discuss the process of hadis narration. Data is then analyzed using qualitative data analysis techniques with a narrative approach. The results of this study indicate that the historical approach allows for a deeper understanding of the political, social, and cultural factors influencing hadis transmission over time. The findings of this research imply the necessity of a more systematic method for assessing the authenticity and validity of hadis based on its historical and social context.